Cultures of professional collaboration: their origins and opponents. Issue 2 (19th April 2017) - Hargreaves, Andy; O'Connor, Michael T.
Abstract : Purpose: This Commentary is a review and critique of arguments that oppose the desirability and impact of professional collaboration in education. The purpose of this paper is to analyze two recent high-profile reviews of professional development and collaboration. The analysis is informed by a historical typology of five phases of professional collaboration in theory and practice. Design/methodology/approach: The Commentary reviews and summarizes selected key texts that represent different phases in the development of advocacy for and research concerning the emergence of professional collaboration. It then critiques the methodology, findings, and recommendations of two key critiques of professional collaboration and development that have been widely disseminated for educators and policymakers. Findings: Contrary to the views of its opponents, professional collaboration as a whole has a record of indirect, long term, yet clear and positive effects on teachers and students. Particular kinds of professional collaboration can vary a great deal in quality and impact, however. Short-term collaborative interventions, such as data teams, are often dependent for their success on the prior existence of deeper cultures and processes. These processes and cultures characterize high-performing systems globally. Advocacy for competitive alternatives is based on insufficient evidence. Originality/value: Although advocacy for more competition in public school systems is common, high-profile critiques of professional collaboration are relatively new. This paper engages with these critiques from a broader historical perspective, and finds they have serious flaws of reasoning and methodology. Thus far, the critiques provide insufficient warrant for moves toward more competitive systems of schooling and teaching.